2022
DOI: 10.1021/acsami.1c24083
|View full text |Cite
|
Sign up to set email alerts
|

Design of Organic-Free Superhydrophobic TiO2 with Ultraviolet Stability or Ultraviolet-Induced Switchable Wettability

Abstract: Superhydrophobic TiO 2 with great application potential is mainly obtained by surface modification with low surface energy organics, which is easily degraded under sunlight irradiation, which results in the loss of superhydrophobic properties. Herein, we developed a room-temperature pulsed chemical vapor deposition (pulsed CVD) method to develop amorphous TiO 2 -deposited TiO 2 nanoparticles. The ultraviolet stability/ultraviolet-induced reversible wettability switch had been simultaneously realized by differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The degradation rate constants of PMMA and PC decreased from 0.36 h À 1 to 0.018 h À 1 and from 0.23 h À 1 to 0.029 h À 1 , respectively, under single UV irradiation for 5 h. It indicates that the TiO 2 coatings prepared by this method can prevent the polymer degradation of PMMA and PC and improve their stability under UV irradiation. Yu et al [85] uses the CVD (pulsed CVD) method to coat amorphous TiO 2 nanoparticles or thin films on the surface of TiO 2 nano-particles at room temperature. It is found that the adsorption stability and the rate of oxygen and the water on surface oxygen vacancies are the keys of facilitating the reversible switching between superhydrophilic and superhydrophobic states, as shown in Figure 7.…”
Section: Chemical Vapor Deposition Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The degradation rate constants of PMMA and PC decreased from 0.36 h À 1 to 0.018 h À 1 and from 0.23 h À 1 to 0.029 h À 1 , respectively, under single UV irradiation for 5 h. It indicates that the TiO 2 coatings prepared by this method can prevent the polymer degradation of PMMA and PC and improve their stability under UV irradiation. Yu et al [85] uses the CVD (pulsed CVD) method to coat amorphous TiO 2 nanoparticles or thin films on the surface of TiO 2 nano-particles at room temperature. It is found that the adsorption stability and the rate of oxygen and the water on surface oxygen vacancies are the keys of facilitating the reversible switching between superhydrophilic and superhydrophobic states, as shown in Figure 7.…”
Section: Chemical Vapor Deposition Methodsmentioning
confidence: 99%
“…83 Copyright 2022, Elsevier. [85] Reproduced with permission Ref. 85 Copyright 2022, American Chemical Society.…”
Section: Chemical Vapor Hydrolysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CVD method [ 36 ] is a modification method to achieve a modification effect by reacting certain substances in the solution with the modified material to form a new substance through a gas-phase reaction to build a roughness or a nano-scale thin film material on the surface of the wood material. The CVD method is a low-cost, simple, and effective method for the preparation of hierarchical micro- and nano-rough structures.…”
Section: The Preparation Of Superhydrophobic Coatings On Woodmentioning
confidence: 99%